Development and Characterization of Quercetin-Loaded Delivery Systems for Increasing Its Bioavailability in Cervical Cancer Cells - Miguel Ferreira; Diana Gomes; Miguel Neto; Luís A. Passarinha; Diana Costa; Ângela Sousa (MDPI AG, 2023)
Quercetin is a natural flavonoid with high anticancer activity, especially for related-HPV cancers such as cervical cancer. However, quercetin exhibits a reduced aqueous solubility and stability, resulting in a low bioavailability that limits its therapeutic use. In this study, chitosan/sulfonyl-ether-β-cyclodextrin (SBE-β-CD)-conjugated delivery systems have been explored in order to increase quercetin loading capacity, carriage, solubility and consequently bioavailability in cervical cancer cells. SBE-β-CD/quercetin inclusion complexes were tested as well as chitosan/SBE-β-CD/quercetin-conjugated delivery systems, using two types of chitosan differing in molecular weight. Regarding characterization studies, HMW chitosan/SBE-β-CD/quercetin formulations have demonstrated the best results, which are obtaining nanoparticle sizes of 272.07 ± 2.87 nm, a polydispersity index (PdI) of 0.287 ± 0.011, a zeta potential of +38.0 ± 1.34 mV and an encapsulation efficiency of approximately 99.9%. In vitro release studies were also performed for 5 kDa chitosan formulations, indicating a quercetin release of 9.6% and 57.53% at pH 7.4 and 5.8, respectively. IC50 values on HeLa cells indicated an increased cytotoxic effect with HMW chitosan/SBE-β-CD/quercetin delivery systems (43.55 μM), suggesting a remarkable improvement of quercetin bioavailability.